Influence of Non - Condensable Gases on the Processes of Heat and Mass Transfer during Film Condensation of Steam in Heat Exchangers - Reshetnikov I.F.; Shikhalev S.V.; Tikhonov S.L. (Problems of the Regional Energetics)
The aim of the article is a quantitative assessment of the influence of non-condensable gases on the intensity of heat and mass transfer processes during film condensation of steam in the specific conditions for heat exchanger. The task is achieved by conducting experimental research of heat and mass transfer processes in film condensation of steam in the presence of non-condensable gases.The study was carried out by the method of stationary heat flow on an experimental kettle with a jacket (0,02 m3 capacity), industrial cooking boilers (0,04 m3 and 0,06 m3 capacity). Cylindrical kettles with a hemispherical and elliptical bottom were selected as the condensation surface. The results of the experiments are presented in the form of a criterion equation for determining the mass transfer coefficient for vapor concentration diffusion. When the concentration of a non-condensable gas reaches 40% an intensification of the resulting heat transfer coefficient from the vapor-gas mixture to the condensation surface is observed. The coefficient of heat transfer to the condensation surface depends on the concentration of non-condensable gases in the apparatus cavity. The results of the research indicate that it is possible to improve the heat exchangers with a jacket and allow an assessment of the heat input when removing the gas mixture from the jacket in the heating mode of the cookers at the design stage. Material research allows to develop automatiс systems and control parameters in the operation of apparatus with a jacket.